Autophagy regulated by the HIF/REDD1/mTORC1 signaling is progressively increased during erythroid differentiation under hypoxia - Li, Jian; Quan, Cheng; He, Yun-Ling; Cao, Yan; Chen, Ying; Wang, Yu-Fei; Wu, Li-Ying (Frontiers in Cell and Developmental Biology, 2022)
For hematopoietic stem and progenitor cells (HSPCs), hypoxia is a specific microenvironment known as the hypoxic niche. The role of hypoxia in maintaining quiescence, self-renewal and proliferation of HSPCs has been more elaborated. What remains unclear is the regulation of hypoxia on HSPC differentiation, especially on the differentiation of HSPCs into erythrocytes. In this study, we show that hypoxia evidently accelerates erythroid differentiation, and in this process effectively enhances autophagy which rapidly supplies cellular components through degradation of organelles or proteins to meet the needs of cell stress or development. In order to ascertain whether autophagy mediates the erythroid differentiation promoted by hypoxia, we analyze the perturbation of erythroid differentiation after pharmacological and genetic interference with autophagy, and address that autophagy is required for hypoxia-accelerated erythroid differentiation. Transcriptomics reveals HIF-1 and mTORC1 pathways may function as the upstream of autophagy to regulate erythroid differentiation under hypoxia. We further determine that mTORC1 signaling is suppressed by hypoxia to relieve its inhibition of autophagy. In addition, we also discover a new regulatory pattern that with the process of erythroid differentiation, mTORC1 activity gradually decreases and autophagy activity increases concomitantly. Moreover, we provide evidence that HIF-1 target gene REDD1, which inhibits mTORC1 activity, is dramatically upregulated under hypoxia. Silencing REDD1 expression activates mTORC1 signaling and impairs the enhanced autophagy and the accelerated erythroid differentiation under hypoxia. Together, our study reveals that hypoxia is conductive to accelerating erythroid differentiation, in which autophagy induced by the HIF-1/REDD1/mTORC1 pathway plays a pivotal role.